Digitalization of Insurance Business Processes on Life Insurance Sales Productivity - Hernady, Joddy; Syafei, M. Yani; Narimawati, Umi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Digital transformation in the insurance industry has become a crucial strategy for improving business efficiency and enhancing sales performance. This study examines the impact of business process digitalization on the productivity of life insurance sales, with agent work efficiency and technology adaptation as mediating variables. The research adopts a quantitative approach with an explanatory research design, using purposive sampling to collect data from insurance agents at MRT Agency- Prudential Indonesia who actively use the PruForce mobile application. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to evaluate the relationships between variables. The findings indicate that business process digitalization positively influences sales productivity, both directly and indirectly, through increased work efficiency and agent technology adaptation. Agents who efficiently manage their tasks and quickly adapt to digital tools demonstrate higher sales performance. These results highlight the importance of equipping agents with appropriate training and technological support to maximize the benefits of digitalization in the insurance sector. This study contributes to the growing body of literature on digital transformation in financial services specifically in the insurance sector and provides practical insights for insurance companies to enhance digital adoption strategies among their sales force